Thumb-Sucking Habits and Oral Health: An Analysis of YouTube Content - Zaki Hakami; Prabhadevi C. Maganur; Sanjeev B. Khanagar; Sachin Naik; Khalid Alhakami; Omar A. Bawazeer; Ahmed Mohammed Alassiry; Satish Vishwanathaiah (MDPI AG, 2022)
This study aims to investigate the content and usefulness of YouTube videos on** thumb-sucking habits. Methods: YouTube was systematically searched for all relevant videos on thumb sucking using primary keywords, such as thumb, finger, and digit sucking. Video information was assessed, such as the type of video, number of likes or dislikes, number of views, and duration of upload. The usefulness of videos was analyzed, and information about treatment modalities was evaluated. Results: A total of 331 YouTube videos (314 educational offerings and 17 testimonials) were included in the analysis. Individual users uploaded (36.6%), followed by healthcare professionals (30.5%). Only 4.83% of the videos were classified as having "very useful" general information content, whereas 51.1% were rated as "slightly useful." There was no significant correlation between the usefulness score and the interaction rate, video length, or viewing rate. The videos advised a psychosocial approach and mechanical or reminder therapy in 32.33% and 25.07% of videos, respectively. Preventive methods accounted for 7.26%, and chemical treatments were discussed in 5.44% of the videos. Conclusion: Information on YouTube about thumb-sucking habits was unsatisfactory and should be improved by oral healthcare professionals and organizations.